Pengaruh remunerasi dan disiplin kerja terhadap kinerja pegawai pada Badan Perencanaan Pembangunan Daerah Kabupaten Lampung Tengah - Silitonga, Doni Tri Saputra; Iskandar, Iskandar (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This research investigates the impact of remuneration and work discipline on employee work quality at the Regional Development Planning Agency (Bappeda) of Central Lampung Regency. This experiment uses multiple linear regression to carry out the analysis. This experiment took 41 ASN staff of Bappeda Central Lampung Regency as samples using the